2015
DOI: 10.1039/c5ra18039b
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted organic syntheses: microwave effect on intramolecular reactions – the Claisen rearrangement of allylphenyl ether and 1-allyloxy-4-methoxybenzene

Abstract: We examined the possible effect microwaves may have on intramolecular reactions such as the Claisen-type rearrangement process carried out in DMSO solvent and in solvent-free microwave irradiation conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…The major species observed were unreacted aryl chloride (46%) and 2-allyl-6-chlorophenol (17%), the Claisen rearrangement product derived from the aryl chloride; Claisen rearrangement of allyloxybenzenes under microwave heating has been reported. 30,31 We also observed the expected CTC coupling product, 1-[2-(2-propen-1-yloxy)phenyl]-2-pyrrolidinone, in 16% yield, along with its Claisen rearrangement product (6%). The remaining identifiable species in the reaction were 1-allyloxybenzene (6%), the hydrodehalogenation product of the aryl chloride, and its Claisen rearrangement product.…”
Section: ■ Introductionmentioning
confidence: 69%
“…The major species observed were unreacted aryl chloride (46%) and 2-allyl-6-chlorophenol (17%), the Claisen rearrangement product derived from the aryl chloride; Claisen rearrangement of allyloxybenzenes under microwave heating has been reported. 30,31 We also observed the expected CTC coupling product, 1-[2-(2-propen-1-yloxy)phenyl]-2-pyrrolidinone, in 16% yield, along with its Claisen rearrangement product (6%). The remaining identifiable species in the reaction were 1-allyloxybenzene (6%), the hydrodehalogenation product of the aryl chloride, and its Claisen rearrangement product.…”
Section: ■ Introductionmentioning
confidence: 69%
“…Claisen rearrangement is accelerated under high-temperature and high-pressure conditions, and the efficacy of MW irradiation to enhance the reaction conversion has been exploited in continuous MW synthesis. Horikoshi et al studied the influence of MW irradiation on the conversion of 1-allyloxy-4-methoxybenzene ( Scheme 5 A, reaction conditions above), 41 as they observed that no significant improvement could be discerned when the reaction was performed under conventional conditions or under MW heating in DMSO. Neat conditions enabled the increase in the yield from 2.5 to 36%, and a two-fold yield improvement was observed compared to the reaction heated in an oil bath.…”
Section: Impact Of High Temperature and Pressure On Homogeneous Organic Synthesismentioning
confidence: 99%
“…of the copper catalyst (entry 19,24). This reaction was performed in the presence of a base and different alcohols acting as both solvent and substrate.…”
Section: Resultsmentioning
confidence: 99%
“…of base and 0.1-0.25 equiv. of the copper catalyst (entry 19,24). Further, the effect of dilution was investigated (Table S5), and it revealed that with the decrease in dilution drastically improved the yield of the desired product B (entry [28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation